(untitled) (Journal of Scientific Research, 2014)
Kidney and gallstones represent a prevalent and costly health problem. This study aimed to define patterns of stones and identify chemical compositions in the sample of symptomatic kidney and gallstones from North-East part of Bangladesh (Sylhet City, Sylhet) using infrared spectroscopy. Kidney and gallstones were recovered from patients of Osmani Medical College and Hospital, Sylhet, Bangladesh. A total of 5 kidney and 3 gall stone samples were collected randomly and analyzed for composition by Fourier Transform Infrared Spectroscopy (FTIR). Among the five kidney stone samples, KDS 01 was mixture of calcium oxalate monohydrate and calcium phosphate, KDS 02 and 03 were calcium oxalate and uric acid stones, KDS 04 was uric acid stone and KDS 05 was calcium oxalate dehydrate and calcium phosphate. Among the three gall stone samples, GBS 01 was cholesterol stone, GBS 02 was mixed stone and GBS 03 was pigment stone. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.16721 J. Sci. Res. 6 (3), 553-561 (2014)